2016
DOI: 10.1002/asl.689
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of incoming biomass burning aerosol plumes over southern Brazil

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…This situation would facilitate the long-range transport of the aerosols from Amazonia to the PO site. Our results add to the understanding of the BB aerosol transport routes in South America and confirm the findings from previous studies on the importance of BB for the boundary layer aerosol budgets-e.g., [15][16][17][18][19][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation would facilitate the long-range transport of the aerosols from Amazonia to the PO site. Our results add to the understanding of the BB aerosol transport routes in South America and confirm the findings from previous studies on the importance of BB for the boundary layer aerosol budgets-e.g., [15][16][17][18][19][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…This region is affected by both local or short-range BB emissions as well as by remote or long-range transport of BB aerosols [11,15]. The long-range tropospheric transport of pollutants is caused by Amazon rainforest wildfires in South America-e.g., [16][17][18][19]. These aerosols and gas-phase species are transported to the south by the South American low-level jet (SALLJ), which is a low-level flow with a jet vertical profile whose maximum intensity is below 1.5 km above ground level (AGL) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been carried out to study atmospheric aerosols, as well as their regional transport (Ulke et al, 2007(Ulke et al, , 2011De Oliveira et al, 2016;Martins et al, 2018;Cúneo et al, 2022). Works of Ulke et al (2007) and Martins et al (2018 have highlighted the influence of the Southern American low-level jet (SALLJ) on the regional transport of smoke plume over South America.…”
Section: Intercontinental Transportmentioning
confidence: 99%
“…Freitas et al (2005) observed that the position of the South Atlantic subtropical high pressure plays an important role in the transport of aerosol plumes from the Amazon region to Southern Brazil. This system also prevents rain-bearing cold fronts from penetrating the area, favouring the accumulation of pollutants and deterioration of the air quality (Oliveira et al, 2016;Targino and Krecl, 2016).…”
Section: Introductionmentioning
confidence: 99%